Detection of trace peroxide explosives in environmental samples using solid phase extraction and liquid chromatography mass spectrometry. Issue 1 (2nd January 2017) - Gamble, Sally C.; Campos, Luiza C.; Morgan, Ruth M.
ABSTRACT: This article presents solid phase extraction (SPE) and liquid chromatography-mass spectrometry (LC-MS) methods for the trace detection of the peroxide explosives triacetone triperoxide (TATP) and hexamethylene triperoxide diamine (HMTD). Furthermore, experimental studies use these methods to explore the efficiency of wastewater treatment plant (WWTP) processes at removing trace levels of peroxide explosives from water samples to assess the application of the developed methods for the detection of explosives in the environment. The principal results of this study showed that the greatest removal of TATP and HMTD from spiked water samples occurred following the biological treatment stage, however, the WWTP processing did not completely remove all of the analytes from the water, suggesting that such chemicals could contaminate downstream river water samples. The toxicity of chemical pollutants is often determined by their concentration, however, even at trace levels, the monitoring of explosives in the natural environment could be extremely informative for the detection of criminal activity as well as long-term effects upon aquatic life. These findings also have significant implications for crime prevention and disruption approaches that can use this type of data as intelligence to guide investigations regarding the source and attribution of detected explosives.